Lipid-modifying therapy and low-density lipoprotein cholesterol goal attainment in patients with familial hypercholesterolemia in Germany: The CaReHigh Registry - Schmidt, Nina; Dressel, Alexander; Grammer, Tanja B.; Gouni-Berthold, Ioanna; Julius, Ulrich; Kassner, Ursula; Klose, Gerald; König, Christel; Koenig, Wolfgang; Otte, Britta; Parhofer, Klaus G.; Reinhard, Wibke; et al. (Atherosclerosis, 2018)
Background and aims - Familial hypercholesterolemia (FH) is amongst the most common genetic disorders encountered in primary care. Yet, only a minority of affected patients is diagnosed and treated. This interim analysis of the CaRe High Registry aims at examining the state of treatment and attainment of lipid goals in German FH patients. - Methods - The CaRe High registry includes FH patients from lipid clinics and private practices. Data have been collected using questionnaires filled in by the recruiting physicians and by interviewing the participating patients. - Results - We examined 512FH patients diagnosed according to clinical criteria. Median age at the time of the first FH diagnosis was 39 (25th and 75th percentile: 27-50) years, median treatment naïve LDL cholesterol (LDL-C) was 239.4mg/dl (6.19mmol/l), 25th to 75th percentile 191.8-342.5mg/dl (4.96-8.86mmol/l). 27% of the participants did not receive lipid-lowering drugs. Among the patients treated with lipid-lowering drugs, 19% received a PCSK9 inhibitor (PCSK9i) in combination with a statin, 9% were treated with a PCSK9i alone and 3% were treated with a combination of PCSK9i and a non-statin drug. Patients with pre-existing CVD were more likely to be treated with lipid-lowering drugs and more likely to receive a PCSK9i, but LDL-C targets were only achieved by a minority of patients (<20%). Gap to target LDL-C was lowest and the median achieved LDL-C reduction was 1.4 times higher with PCSK9i treatment than with (oral) lipid-lowering therapy without PCSK9i. - Conclusions - The Care High registry has included patients with the typical clinical features of familial hypercholesterolemia. PCSK9i treatment in addition to standard therapy allows attainment of target values in many patients with initially very high LDL-C.